Features of Gothic Literature in “Great Expectations” By Charles Dickens (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the features of Gothic literature in Great Expectations by Charles Dickens. Gothic literature often includes dark and mysterious settings, strange characters, and themes of fear and suspense. In this novel, Dickens uses eerie places like Satis House and the misty marshes to create an unsettling atmosphere. The characters, such as the mysterious convict Magwitch and the tragic Miss Havisham, reflect Gothic traits of secrecy and emotional extremes. Themes of guilt, isolation, and mystery also play an important role in shaping the story. By mixing Gothic elements with his usual social commentary, Dickens creates a unique narrative that captures both the imagination and the emotions of the reader.